Integrated metabolic, transcriptomic and chromatin accessibility analyses provide novel insights into the competition for anthocyanins and flavonols biosynthesis during fruit ripening in red apple - Cheng, Chunzhen; Guo, Ziwei; Li, Hua; Mu, Xiaopeng; Wang, Pengfei; Zhang, Shuai; Yang, Tingzhen; Cai, Huacheng; Wang, Qian; Lü, Peitao; Zhang, Jiancheng (Frontiers in Plant Science, 2022)
Fruit ripening is accompanied by a wide range of metabolites and global changes in gene expression that are regulated by various factors. In this study, we investigated the molecular differences in red apple ‘Hongmantang’ fruits at three ripening stages (PS1, PS5 and PS9) through a comprehensive analysis of metabolome, transcriptome and chromatin accessibility. Totally, we identified 341 and 195 differentially accumulated metabolites (DAMs) in comparison I (PS5_vs_PS1) and comparison II (PS9_vs_PS5), including 57 and 23 differentially accumulated flavonoids (DAFs), respectively. Intriguingly, among these DAFs, anthocyanins and flavonols showed opposite patterns of variation, suggesting a possible competition between their biosynthesis. To unveil the underlying mechanisms, RNA-Seq and ATAC-Seq analyses were performed. A total of 852 DEGs significantly enriched in anthocyanin metabolism and 128 differential accessible regions (DARs) significantly enriched by MYB-related motifs were identified as up-regulated in Comparison I but down-regulated in Comparison II. Meanwhile, the 843 DEGs significantly enriched in phenylalanine metabolism and the 364 DARs significantly enriched by bZIP-related motifs showed opposite trends. In addition, four bZIPs and 14 MYBs were identified as possible hub genes regulating the biosynthesis of flavonols and anthocyanins. Our study will contribute to the understanding of anthocyanins and flavonols biosynthesis competition in red apple fruits during ripening.